The Correlation Between Plasma Malondialdehyde And Homocysteine Levels in Preeclamptic Patients - Tuğ, Niyazi; Çıkım, Gürkan (Fırat University, 2002)
Aim: To investigate the possible correlation between plasma malondialdehyde and homocysteine concentrations in preeclamptic patients. Metarial and Methods: Venous blood samples of 40 women, 20 were preeclamptics and 20 were healthy pregnant controls were collected. Plasma malondialdehyde and homocysteine concentrations were measured and the correlation between them was investigated. Mann Whitney U test and Spearman correlation analysis were used for statistical analysis. Results: Plasma malondialdehyde and homocysteine concentrations were higher in preeclamptic patients (p1, p2

Amaç: Preeklamptik hastalarda plazma malondialdehid ve homosistein konsantrasyonları arasındaki olası ilişkinin incelenmesi. Gereç ve Yöntem: Çalışmada 20 preeklamptik, 20 normal gebe olmak üzere toplam 40 gebeden venöz kan örnekleri toplandı. Plazma malondialdehid ve homosistein düzeyleri belirlenerek aralarındaki korelasyon araştırıldı. İstatistisel incelemelerde Mann Whitney U testi ve Spearman bağıntı analizi kullanıldı. Bulgular: Malondialdehid ve homosistein düzeylerinin preeklamptik hastalarda artmış olduğu saptandı (p1, p2
PREEKLAMPTİK HASTALARDA PLAZMA MALONDİALDEHİD VE HOMOSİSTEİN DÜZEYLERİ ARASINDAKİ KORELASYON